Exploring Place Attachment And Migration Dynamics: Insideness Vs Outsideness In The Indian Sundarbans (Journal of Namibian Studies : History Politics Culture, 2023)
This study delves into the nuanced dynamics of place attachment and migration patterns within the Sundarbans region, examining the interplay between insideness and outsideness. Employing a mixed-methods approach, the research integrates quantitative analysis of survey data with qualitative insights derived from interviews and field observations. Methodologically, the study utilizes Guttman scaling to systematically measure place attachment, offering a comprehensive understanding of respondents' affinities and priorities. Additionally, a place response test is conducted to assess residents' preferences for alternative living arrangements, illuminating the complexities of insideness versus outsideness in their decision-making processes. The findings unveil contrasting patterns of place attachment and migration preferences between riverine and non-riverine villages, shedding light on the differential impacts of environmental dynamics on individuals' sense of belonging. Furthermore, the study identifies the role of insideness and outsideness in shaping migration patterns, with villages like Purandar, located in market areas, demonstrating a propensity for outmigration among the younger population. This trend is driven by the allure of urbanization and economic opportunities, highlighting the complex interplay between internal and external factors in shaping individuals' attachment to place. Overall, this research underscores the significance of considering insideness and outsideness in understanding place attachment and migration decisions.